Fintech Supporting Sharia Rural Bank - Nasfi, Nasfi; Yunimar, Yunimar; Prawira, Adi; Aziz , Zakaria; Lutri , Ahmad (Journal of Industrial Engineering & Management Research, 2022)
The purpose of this study is to see how much influence fintech has on the operational development of Sharia Rural Bank or BPRS in an area, in West Sumatra. Fintech is an innovation in the field of financial services or banking financial institution services, one of which is to support financial inclusion programs. The development of digital financial technology, including in the Islamic financial services industry, undeniably affects financial mechanisms in operational activities, especially in financing products. Fintech is a potential economic force to be developed in the territory of the Unitary State of the Republic of Indonesia which consists of thousands of islands. With the development of technology, especially fintech, Sharia Rural Bank or BPRS must follow or adjust financing services to debtors and prospective debtors by adopting fintech in operational activities. Technological developments that require BPRS to follow and adjust services to debtors (mudharib) so that BPRS can grow and develop.